"Love and compassion not found Elsewhere": A Photovoice exploration of restorative justice and nonviolent communication in a community-based juvenile justice diversion program. (October 2020) - McMahon, Sheila M.; Pederson, Shelby
Highlights: Nonviolent communication (NVC) supports at-risk youth in conflict resolution. NVC improves interpersonal communication among justice-system involved youth. A trauma-informed approach to NVC improves restorative programming. NVC can help youth improve in academic performance and persistence. Restorative practices support social connection among youth in a diversion program. Abstract: This research study used Photovoice methodology to investigate the impact of a trauma-responsive restorative justice program for youth involved with the juvenile justice system. The 14-week program in Florida uses restorative circle practice and training in nonviolent communication (NVC) to build relationships among a diverse body of youth (ages 11–18) in order to decrease recidivism, as well as to promote individual and community well-being. Participants used smartphones to capture and share images about the program. Through a focus group circle dialogue and written quotes, participants described the how the program has helped them to grow in empathy and confidence, resolve interpersonal conflicts, and strengthen relationships. This study contributes to the literature on community-based interventions for at-risk youth by sharing a program that has benefits for youth participants and the larger community. Findings may be used to guide participatory multi-racial, multi-generational community-based restorative interventions to support at-risk youth.